NodeMcu Microcontroller Based Disinfectant Fluid Monitoring System Using Water Level Control Sensor and Ultrasonic Sensor - Rama Sahtyawan; Andika Bayu Saputra; Syaeful Arief (Institut Teknologi Dirgantara Adisutjipto, 2020)
The spread of the coronavirus (Covid-19) in Indonesia is increasing.Â Many innovations have begun to emerge between the use of chambersÂ that are placed on the streets is rampant, the village gate is still manually with an officer pressing the switch for incoming guests, and there is also spraying that is done automatically, reads guests who come, automatically, the obstacles encountered are sometimes run out of disinfectant fluid, demanding officers must regularly check so as not to run out. This research will develop an IoT-based disinfecting booth in addition to spraying disinfecting liquid automatically. It can also fill disinfecting liquid automatically and can be monitored via a Smartphone. System and tool requirements consist of NodeMcu Esp 8266, flow water sensor, ultrasonic sensor, Relay, Solenoid Valve, Arduino IDE, Blynk Apps, ThingSpeak The process of detecting disinfectant fluid level is divided into 2, safe level with water level between 11-50 cm, The danger level with the water level between 0-10 cm. Then the node sends an output signal to the relay. The relay continues that signal, which functions as a switch to open the solenoid, water will flow through the pipe when the solenoid valve is opened so that the water tap is open to fill the derijen. The Thingspeak IoT platform is used to display disinfectant liquid level graphs. Sensor output data will be reported in real-time to the admin via the application of the Blynk app. With the development of this device, it is expected to reduce the spread of the COVID-19 virus.